UPAYA PENINGKATAN PERFORMANCE MESIN SCREW PRESS BERDASARKAN NILAI IDLING DAN MINOR STOPPAGES DAN REDUCED SPEED DI PABRIK KELAPA SAWIT KAPASITAS 30 - Pada Mulia Raja; Zulham Effendi; Calvin Arnico Lase (Institut Teknologi Sawit Indonesia (ITSI), 2022)
Palm oil processing in the Palm Oil Mill (PKS) is carried out by extracting the fruit flesh (mesocarp) of the oil palm fruit in the palm oil mill processing with a palm oil mill processing machine. Realizing the results of palm oil processing requires a machine that operates in good condition to produce the output the machine is following the desired achievement with good screw press machine performance without any problems experienced during processing. This research was conducted by direct observation of the state of the screw press machine and taking daily secondary data in the form of loading time data, total production, production targets, ideal cycle time, actual, cycle time, downtime, operation time, and problem data on the screw press machine for 6 months from June-November 2020 on 2 screw press. From the results of the study, it was found that the constraints that caused the low-performance value of the screw press machine based on the value of idling and minor stoppages and reduced speed which resulted in the machine often experiencing momentary stops and a decrease in rotation of the screw press every month due to the large capacity of the machine that was not following the capacity. factory and the condition of the machine and the lack of supervision and control in humans cause the machine to often experience a decrease in performance on the screw press machine. From the results of the analysis of the results carried out, it was found that alternative solutions to improve the performance of the screw press machine were caused by 4 factors based on the identification carried out using a cause-and-effect diagram by paying attention to the critical point of a machine caused by human factors, machines, materials and methods based on analysis. Screw press machine performance is based on the value of idling and minor stoppages and reduced speed.